SPECIFICATIONS FOR THE MODEL 42 SNOW MIXER - Pierce, N. E. (1963)
Outline specifications for procurement of special equipment for compaction of snow in polar regions are being prepared by the laboratory. This technical note contains the specifications for the model 42 snow mixer. This unit, which is a ski mounted, towed-type piece of equipment, is used to pulverize and intermix (depth-process) the natural snow. The model 42 snow mixer is especially suitable for use in deep snow fields where its 42 inch depth can be used to produce a snow mat up to 28 inches thick for greater load bearing capacity.